AN ANALYSIS OF SYMBOLS IN NOVEL THE MIDNIGHT LIBRARY BY MATT HAIG - Kamil Setiawati; Hardiany, Dewi Rosnita (Praniti: Jurnal Pendidikan, Bahasa, dan Sastra, 2023)
Language is a part of our life, we live in a sea of languages and most of our interactions are done using language. Language is a symbolic system in which words are associated with objects, ideas, and action.. The objective of the study is to analyze the symbols in The Midnight Library by Matt Haig. The data in this study is qualitative. In conducting this research, a researcher used Carl Jung's theory of archetypal image, as described in a book by in a book by Guerin (2005).The fourteen symbols: water, sun, color, circle, serpent, number, the archetypal woman, the demon lover, the wise old man, the trickster, garden, tree, desert, and mountain. The resercher is done by classifying the semiotic elements, namely the symbols. In the novel The Midnight Library finds 14 symbols based on the result of the analysis data. The circle symbol appeared 75 times in this novel. It can be concluded that in the novel The Midnight Library by Matt Haig there are 14 symbols and the frequently used symbol is circle.